Impact of different storage containers on seed quality parameters of eggplant (Solanum melongena) during storage - NISHA; BHUKER, AXAY; SINGH, NIRMAL; SINGH, GAGANDEEP; AKASH; SOURABH; KUMAR, MUKESH; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to assess the impact of natural ageing and different storage containers on eggplant (Solanum melongena L.) seed quality during the 2020–21 and 2021–22 winter (rabi) seasons. Genetically pure seeds were used and stored in cloth and polythene bags. Seed quality parameters (germination, seedling length, seedling dry weight, and seed vigour) were monitored at various intervals (0, 3, 6, 9, 12, 15, 18 months). Freshly harvested seeds (control) exhibited superior quality, with higher germination rates, longer seedlings, greater seedling dry weight, and improved vigour indices compared to stored seeds over 18 months. Seed quality deteriorated with longer storage, reaching its lowest point at 18 months. Among storage containers, cloth bags showed a faster decline in seed quality compared to polythene bags (>700 gauge). In field experiments, one-year stored seeds from polythene bags outperformed those from cloth bags in terms of seed establishment percentage, mean emergence time, and germination speed. In conclusion, polythene bags maintained acceptable seed germination (meeting IMSCS standards) for up to 15 months, while cloth bags maintained it for up to 12 months. Therefore, polythene bags are a better choice for preserving eggplant seed quality during storage, particularly for longer durations.